Penggunaan WhatsApp sebagai Media Komunikasi Pembelajaran Bahasa Inggris - Hartatik, Sri Fatmaning; Lestari, Hernina Dewi (Universitas Merdeka Malang, 2021)
This qualitative study intended to describe the use of WhatApp (WA) as a communication channel used in teaching English as a Foreign Language, especially in Speaking class at 2020/2021 academic year. To gain the data, the reserachers interviewed two teachers teaching two different Speaking classes and observed the communication happened during teaching and learning process within WA group in which 23 students participated in each class. The results of interview showed that the use of WA as communication channel in teaching and learning process was based on some reasons as all participants had this application and could operate this application well; WA offered complete fitures that could facilitate teaching and learning as well as communication process; this application was considered to be less internet data consuming so it would not burden the participants. In addition, the results of observation showed that the verbal and non verbal communication performed by WA participants accommodated social, ritual, expressive, and instrumental communication functions which led to sustainable communication and intimacy amongst the members. Regarding the posstive sides of WA, the researchers suggest all educators to make use WA in their online learning. Besides, the further researchers are encouraged to conduct further investigation on WA implementation in order to broader the knowledge of communication in education. Keywords: Communication, Education, WhatsApp, Communication ChannelsDOI:Â https://doi.org/10.26905/nomosleca.v7i1.5535